The "power few" of missing persons' cases. Issue 2 (9th March 2020) - Huey, Laura; Ferguson, Lorna; Kowalski, Larissa
Abstract : Purpose: The purpose of this paper is to test the "power few" concept in relation to missing persons and the locations from which they are reported missing. Design/methodology/approach: Data on missing persons' cases ( n = 26, 835) were extracted from the record management system of a municipal Canadian police service and used to create data sets of all of the reports associated with select repeat missing adults ( n = 1943) and repeat missing youth ( n = 6, 576). From these sources, the five locations from which repeat missing adults and youth were most commonly reported missing were identified ("power few" locations). The overall frequency of reports generated by these locations was then assessed by examining all reports of both missing and repeat missing cases, and demographic and incident factors were also examined. Findings: This study uncovers ten addresses (five for adults; five for youths) in the City from which this data was derived that account for 45 percent of all adults and 52 percent of all youth missing person reports. Even more striking, the study data suggest that targeting these top five locations for adults and youths could reduce the volume of repeat missing cases by 71 percent for adults and 68.6 percent for youths. In relation to the demographic characteristics of the study's sample of adults and youths who repeatedly go missing, the authors find that female youth are two-thirds more likely to go missing than male youth. Additionally, the authors find that Aboriginal adults and youths are disproportionately represented among the repeat missing. Concerning the incident factors related to going missing repeatedly, the authors find that the repeat rate for going missing is 63.2 percent and that both adults and youths go missing 3–10 times on average. Practical implications: The study results suggest that, just as crime concentrates in particular spaces among specific offenders, repeat missing cases also concentrate in particular spaces and among particular people. In thinking about repeat missing persons, the present research offers support for viewing these concerns as a behavior setting issue – that is, as a combination of demographic factors of individuals, as well as factors associated with particular types of places. Targeting "power few" locations for prevention efforts, as well as those most at risk within these spaces, may yield positive results. Originality/value: Very little research has been conducted on missing persons and, more specifically, on how to more effectively target police initiatives to reduce case volumes. Further, this is the first paper to successfully apply the concept of the "power few" to missing persons' cases.